Prevalence of Overweight and Obesity in the Middle-age Population: A Priority for the Health System - Mehdi KHABAZKHOOB; Mohammad Hassan EMAMIAN; Hassan HASHEMI; Mohammad SHARIATI; Akbar FOTOUHI (Tehran University of Medical Sciences, 2017)
Background: The aim of this study was to determine the prevalence of overweight and obesity and their associated factors in the middle-aged population of Shahroud, North of Iran. Methods: In a population-based cross-sectional study with random cluster sampling, 300 clusters of Shahroud (north of Iran) were randomly selected from the 40-64 yr old population of the city, during 2009 and 2010. Upon enrollment, participants were weighed on digital scales and their heights were measured under standard conditions. Overweight and obesity were defined as a body mass index (BMI) of 25-29.9 kg/m2 and a BMI ≥30 kg/m2, respectively. Results: Of the 6311 selected people, 5190 people (82.2%) participated in the study. Their mean age was 50.9±6.2 yr, and 2977 of them were women (57.4%). Age and gender standardized mean BMI in the study population were 28.1 kg/m2 (95% CI: 27.9-28.2). Age and gender-standardized prevalence of BMI≥25 was 74.4% (95% CI: 73.0-75.8); 43.4% (95% CI 44.8-42.0) were overweight and 31.0% (95% CI 32.5-29.6) were obese. Overweight, Obesity and a BMI ≥25 prevalence's were significantly higher in women (P<0.001). In the multiple logistic regression models, female gender and higher economic status were significantly correlated with BMI≥25. In addition, people over the age of 54 yr were more likely to have BMI≥25 than those in the 40-44 yr age range (P<0.001). Conclusion: The prevalence of overweight and obesity in the present study, especially in women, was higher than that reported from previous studies in Iran. Considering prevention, programs for overweight and obesity-related are suggested as a priority for the health system in this population.